Nucleosome remodelling: structural insights into ATP-dependent remodelling enzymes. Issue 1 (9th April 2019) - Sundaramoorthy, Ramasubramanian
Abstract : ATP-dependent chromatin remodelling enzymes play a fundamental role in determining how nucleosomes are organised, and render DNA sequences accessible to interacting proteins, thereby enabling precise regulation of eukaryotic genes. Remodelers conserved from yeast to humans are classified into four families based on the domains and motifs present in their ATPase subunits. Insights into overall assembly and the mode of interaction to the nucleosome by these different families of remodelers remained limited due to the complexity of obtaining structural information on these challenging samples. Electron microscopy and single-particle methods have made advancement and uncovered vital structural information on the number of remodelling complexes. In this article, we highlight some of the recent structural work that advanced our understanding on the mechanisms and biological functions of these ATP-dependent remodelling machines.